Conservative leaders, coalition, and Britain's decision for war in 1914 - Young, John W. (Taylor & Francis (Routledge), 2014)
Conservative leaders may have had a decisive impact on the decision by the Liberal government to enter the Great War in August 1914. In a seminal article of 1975 Keith Wilson argued that their readiness to fight ‘cut the ground … from beneath the feet of the non-interventionists’ in the Cabinet. Those ministers who had hitherto opposed war now recognised that continued divisions could bring the Government’s collapse, in which case the Unionists, probably in a coalition with pro-war Liberals, would take office and enter the conflict anyway. Since Wilson’s essay important light has been shed on Unionist thinking by works that look at the July Crisis as part of a longer party history. The purpose of this article is to provide a detailed investigation of the actions of Unionist leaders in the days immediately leading to war. In so doing it will seek to resolve some of the main contradictions in the primary evidence, argue that the possibility of a coalition was very real and demonstrate that one key player – the First Lord of the Admiralty, Winston Churchill – subsequently tried, with some success, to disguise his activities.